The practice of sports physical activity and its reflection on the prevention of aggressive behavior among secondary school students - تكركارت فيصل; أوشن بوزيد (sports creativity, 2025)
The study centered on sports physical activity and its reflection on aggressive behavior. We were able to complete this research, which aims to try to determine the extent of the role of sports physical activity in preventing aggressive behavior and the extent of its contribution to preparing the good individual in all its aspects and trying to identify the problems of teenage pupils and develop The educational family is on the right path towards knowing the status of physical and sports activity in addressing the problems of students in the secondary stage, and the study was applied to a sample of 91 students in the secondary stage in the municipality of oulad Uday elgbala of the midwifery and used in this research the questionnaire tool where the results showed that the practice of physical sports activity has a role in Reducing the physical and verbal aggressive behavior of secondary school students. As well as it has a role in consolidating the relationship between the student and his colleagues and the elements of the educational community on the other hand, and the statistical significance test "X²" was employed at the significance level of 0.05, which confirms the validity of the proposed hypotheses, and the study came out with a set of recommendations, the most important of which is spreading the culture of practicing physical physical activity in order to Reject violence and aggressive behavior with benign behavior such as cooperation and sportsmanship